UPAYA PENINGKATAN HASIL BELAJAR LARI JARAK PENDEK MELALUI PERMAINAN GOBAG PERANG (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2015)
The purpose of this study was to determine the learning outcome Elementary School fourth grade students Sumbaga 03 districts Bumijawa Tegal regency 2013/2014 school year through learning sprinting meelalui gobag war game. This research is a class act consisting of two cycles where each cycle consists of four stages: planning, action, observation (observation) and reflection. Data collection techniques in this study using observational assessment liveliness attitudes of students, completeness assessment of learning outcomes, as well as students' questionnaire responses or responses through data analysis using descriptive analysis techniques percentage. The observation of the learning process that is to do with the attitude of the students during the learning activity, the results of the first cycle of 72.00% and the percentage of second cycle results percentage of 92.00%, of these results there is an increase of 20.00%. While the completeness of student learning outcomes through the results of this study showed that an increase in cycle I reached 58.33% and cycle II reached 91.67%, of these results there is an increase of 33.34%. And from analysis of student questionnaire responses received a positive response from the students, it can be seen from the average value of 78.83% of students.